2009
DOI: 10.17221/107/2009-pse
|View full text |Cite
|
Sign up to set email alerts
|

The effect of zeolite, organic and inorganic fertilizers on soil chemical properties, growth and biomass yield of apple trees

Abstract: The objective of this study was to evaluate the influence of organic (cattle manure) and inorganic fertilizers [composite NPK (15:15:15)] and natural zeolites on soil properties, vegetative growth and yield of apple plants grown on vertisol under Cacak conditions (Western Serbia). The results showed that the combined fertilization induced a decrease in acidity, an increase in humus content, a partial increase in total nitrogen (N TOT ), and, primarily, a rise in available phosphorus (P) and potassium (K) leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(21 citation statements)
references
References 13 publications
2
19
0
Order By: Relevance
“…The combined application of farm manure and mineral fertilizer could induce an increase in the humus content, nitrogen, and available phosphorus and potassium levels (Gondek andFilipek-Mazur 2005, Verma et al 2012). As a result of an increase in nutrient level of soil, a significant effect (P ≤ 0.05) on yield per hectare was determined (Milosevic and Milosevic 2009). Our results are also in agreement with Matula and Pechová (2007).…”
Section: Resultsmentioning
confidence: 99%
“…The combined application of farm manure and mineral fertilizer could induce an increase in the humus content, nitrogen, and available phosphorus and potassium levels (Gondek andFilipek-Mazur 2005, Verma et al 2012). As a result of an increase in nutrient level of soil, a significant effect (P ≤ 0.05) on yield per hectare was determined (Milosevic and Milosevic 2009). Our results are also in agreement with Matula and Pechová (2007).…”
Section: Resultsmentioning
confidence: 99%
“…also observed improved soil water content and temperature changes in the root zone area of high density guava cultivation under subtropical climatic condition. Moreover, Milosevic & Milosevic (2009) also observed that applications ____________________________________________________________________________________________________________________ of inorganic fertilisers along with organic manures enhanced the nutrient use efficiency ensuring better vegetative growth of trees, higher yields and quality of apple fruits. …”
Section: Growth Yield and Fruit Quality Of Guavamentioning
confidence: 88%
“…Zeolite also improved soil aggregate, prevented moisture content, induced soil remedy from heavy metal-acidic soil pollutant (Jakab, S. & Jakab, A., 2010). The application of zeolite for vegetative growth and yield improvement has also been reported in apple (Milosevic & Milosevic, 2009), corn (Ippolito, Tarkalson, & Lehrsch, 2011 and kale (Brassica albograbra) (Li, Wee, & Sohn, 2013).…”
Section: Plant Growth Improvement and White Rust Incidencementioning
confidence: 89%